Effect of long working hours and insomnia on depressive symptoms among employees of Chinese internet companies - Xiaoman Liu; Chao Wang; Jin Wang; Yuqing Ji; Shuang Li (BMC, 2021)
Abstract Background In China, long working hours and insomnia are relatively common among internet company employees. Considering that both can affect mental health, we examined their independent and interaction effects on these employees' depressive symptoms (DS). Methods We analyzed data from the 2016 occupational health questionnaire survey conducted in 35 large-, medium-, and small-scale internet companies. Overall, 3589 full-time employees were recruited to evaluate the association among working hours, insomnia, and DS. The Patient Health Questionnaire (PHQ-9) was used to assess DS. The association of DS (PHQ-9 ≥ 10) with working hours (≤40, 41-50, 51-60, and > 60 h/week), insomnia (with or without), and interaction of both was estimated using multivariable logistic regression analysis. Results Compared with the group working for ≤40 h/week, the adjusted odds ratios (ORs) for DS among participants who worked for 41-50 h/week, 51-60 h/week, and > 60 h/week were 1.32 (1.11-1.56), 1.74 (1.35-2.24), and 2.54 (1.90-3.39), respectively. The ORs for DS among those with insomnia were 2.36 (2.04-2.74) after adjusting for general characteristics. The ORs for DS related to insomnia were similar [1.91 (1.46-2.50), 2.00 (1.61-2.50), respectively] in the participants who worked for < 50 h/week. However, among participants working for 51-60 h or > 60 h/week, the adjusted ORs for DS substantially increased to 4.62 (2.90-7.37) and 5.60 (3.36-9.33), respectively. Moreover, among the participants with insomnia, working overtime showed a greater association with DS. Conclusions We showed that long working hours and insomnia are independent factors associated with the prevalence of DS; furthermore, an interaction effect of long working hours and insomnia on DS was observed. For relieving DS in internet company employees, it is important to reduce insomnia.